QASHQADARYO VILOYAT TA’LIM TIZIMIDAGI AHVOL: MUAMMO VA ZIDDIYATLAR(XX asr 80-yillarida) - Jomurodov, O.S (Social science and innovation, 2024)
In the years after the war, the field of public education was considered as the main link of the social system, and a certain amount of attention was paid to it. The technical equipment of the schools, the demand level of the buildings, water supply, etc. do not meet the modern requirements and world standards, which in turn had a negative impact on the educational process. A mood of indifference appeared among the students. The scientific centers opened in the southern regions of Uzbekistan progressed despite difficulties, played a positive role in the development of the education system, raising the cultural level of the population, and providing the national economy with teaching personnel.